The Mediating Role of Risk Management and Networking Capabilities: Relationship With Human Capital, Dynamic Capabilities, and Business Performance - A Study of State- Owned Banking In Manokwari, West Papua - Lambi, Manuel; Echdar, Saban; Ansar, Ansar; Baharuddin, Baharuddin (Green Publisher Indonesia, 2025)
This study aims to examine the role of Risk Management Mediation and Network Capabilities, the relationship with Human Capital, Dynamic Capabilities and Business Performance in SOE Banking in Manokwari, West Papua Province. The sample of this study is 206 respondents from state-owned banking employees in Manokwari, West Papua. The research data was obtained from filling out questionnaires and analyzed using SEM-AMOS analysis. The results of the study showed: (1) Human capital and dynamic ability have a positive and significant effect on risk management and network capability; (2) Human capital does not have a significant effect on business performance; (3) Dynamic capabilities have a significant effect on business performance; (4) Risk management and network capabilities have a significant effect on business performance; 5) Human capital does not have a significant effect on business performance through risk management; (6) Human capital and dynamic capabilities have a significant effect on business performance through network capabilities.